Exploring the incidence and causes of cesarean Delivery : Partially Mixed Concurrent quantitative and Qualitative analysis from a Medical College - Ahmad, Ayesha; Khatoon, Fareha; Nishad, Suman; Saambhavi, -; Sonam, Sonali (Bangladesh Journal of Medical Science, 2022)
Background: India has seen a rise in the incidence of cesarean deliveries (CD) especially in the last decade. The present national average stands at 17.2%, which if taken as a stand alone figure represents an almost ideal statistical measurement. However, the country has widespread regional variations in the CD rate, ranging from 4.4% to 35.9%. Auditing individual CD rates by each institution, and exploring reasons for high incidence remains an essential component of maternal care. Aim of the study: The present study was done to find out the incidence of CD at our facility, compare it with the national average and explore reasons for high incidence of CD. Methodology: It is a partially mixed concurrent quantitative and qualitative study including retrospective analysis of one year data and filling up of questionnaire from resident doctors. Data extraction was done from Maternity Ward, for all women who delivered during the aforementioned period in our facility, including socio-demographic profile, number of births, mode of delivery, reasons for induction of labour and any complications during childbirth. Statistical analysis was done using appropriate tests. Results: A total of 621 deliveries were studied, out of which 44.6% delivered vaginally and 55.3% had CD. Conclusion: The incidence of CD in the present study is 55.3% . The main reasons for high incidence of CD are high risk pregnancies, previous CD, fear of litigation and logistical delays in performing Category I cesarean section, prompting early decision for CD. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 284-290